Efeitos cardiorrespiratórios da administração subaracnóide de cetamina ou da associação com ifenprodil em equinos anestesiados com sevofluorano - Zangirolami Filho, Darcio [UNESP] (2014)
The application of anesthetic or analgesic drugs through the spinal via has been employed as an adjunct to inhalational anesthesia with the aim of increasing visceral and/or somatic, intra-and postsurgical analgesia. The antagonists of N-methyl-D-aspartate receptors have been currently used for the prevention of pain induced by surgical procedures, but it is unknown whether the use of such therapeutics, especially through subarachnoid space may be deleterious to the homeostasis of horses kept under anesthesia with sevoflurane. Ten healthy horses (317 ± 27 kg) with no defined breed, were allotted into three groups and subjected to anesthesia induction with 60 mg/kg/IV of guaiacol glyceryl ether, 0.1 mg/kg of midazolam and 3mg/Kg of propofol. Animals were subjected to inhalation anesthesia with sevoflurane, whose final expiratory concentration was maintained at 2.8%. After reaching this concentration it was applied by subarachnoid via through a previously implanted catheter one of the following treatments: 0.9% NaCl (S group), 0.5 mg ketamine/kg (KS group) or 0.5 mg ketamine/kg associated with ifenprodil 0.015 mg/ kg (Ki group). The moments of evaluation after application were: MB (baseline evaluation), Mind (eight minutes after induction), M1.2 (alveolar concentration of 2.8%), Mtrat (2.5 min after treatment) and at moments M5 to M60 (5, 10, 15, 20, 25, 30, 45 and 60 minutes after treatment ). Cardiorespiratory and blood gas parameters, as well as anesthetic induction and recovery scores were evaluated. Data obtained from each group and between groups were subjected to variance analysis with multiple repetitions, followed by Newman-Keuls Student test. For induction and recovery scores analyzes the Kruskal-Wallis test was used. For all analyzes a p˂0.05 was considered as statistically significant. As for anesthetic induction 17% ( n = 3) of all animals received a score of 3 (acceptable) and ...